Artificial chromosome technology and its potential application in plants - Kan, Manman; Huang, Tengbo; Zhao, Panpan (Frontiers in Plant Science, 2022)
Plant genetic engineering and transgenic technology are powerful ways to study the function of genes and improve crop yield and quality in the past few years. However, only a few genes could be transformed by most available genetic engineering and transgenic technologies, so changes still need to be made to meet the demands for high throughput studies, such as investigating the whole genetic pathway of crop traits and avoiding undesirable genes simultaneously in the next generation. Plant artificial chromosome (PAC) technology provides a carrier which allows us to assemble multiple and specific genes to produce a variety of products by minichromosome. However, PAC technology also have limitations that may hinder its further development and application. In this review, we will introduce the current state of PACs technology from PACs formation, factors on PACs formation, problems and potential solutions of PACs and exogenous gene(s) integration.